2017
DOI: 10.2337/dc16-1458
|View full text |Cite
|
Sign up to set email alerts
|

BMI and All-Cause Mortality in Normoglycemia, Impaired Fasting Glucose, Newly Diagnosed Diabetes, and Prevalent Diabetes: A Cohort Study

Abstract: U-curve relationships existed regardless of diabetes status. Optimal BMI for lowest mortality became gradually higher with worsening diabetes for each sex and each age-group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 36 publications
(50 reference statements)
7
55
1
Order By: Relevance
“…However, this study had inadequate statistical power because it included only 507 patients with diabetes 26. The Korean Metabolic Risk Factor Study observed a U-curved relation between BMI and 10-year all-cause mortality regardless of diabetes status 27. Among 12 million Korean adults, the optimal BMI for the lowest mortality increased with worsening diabetes for both sexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study had inadequate statistical power because it included only 507 patients with diabetes 26. The Korean Metabolic Risk Factor Study observed a U-curved relation between BMI and 10-year all-cause mortality regardless of diabetes status 27. Among 12 million Korean adults, the optimal BMI for the lowest mortality increased with worsening diabetes for both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the BMI–mortality association among Asian patients with diabetes (Japan,26 Korea27 and China28–30) is limited. The Jichi Medical School Cohort Study reported a high risk of 10-year all-cause mortality for Japanese patients with diabetes with leanness (BMI 14.2–21.1 kg/m 2 ) regardless of age.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the inaccuracy of self‐reported BMI measurements may be partially responsible. Third, the older age of the participants may have also contributed to the weak associations in some studies, because the associations of BMI are generally weaker at older ages …”
Section: Discussionmentioning
confidence: 99%
“…ALT and AST were measured using the nicotinamide adenine dinucleotide‐ultraviolet (NADH‐UV) absorption method or the Reitman‐Frankel method. Fasting serum glucose was assayed using enzymatic methods . Blood pressure was measured using a standard mercury sphygmomanometer.…”
Section: Methodsmentioning
confidence: 99%
“…In the current prospective cohort study, we identified HCC incidence according to risk factors. We then examined the associations between potential risk factors and HCC and studied whether the associations differed by age, sex, or liver disorder status …”
Section: Introductionmentioning
confidence: 99%